Dental trauma in toddlers 1–3 years of age living in multicultural areas of Stockholm, Sweden: A retrospective cohort study. Issue 4 (10th April 2021) - Anderson, Maria; Duran Sahin, Demet; Tsilingaridis, Georgios
Abstract: Background/Aim: Traumatic dental injuries are common and affect many children. The aim of this retrospective study was to investigate the prevalence and characteristics of dental trauma as well as the costs and resource use in a cohort of children aged 1–3 years in low socioeconomic areas (low income and educational level) of Stockholm. Materials and Methods: Data were extracted from a larger intervention trial and analyzed for the prevalence and other characteristics of dental trauma as well as patient characteristics of children ( n  = 1346) from six dental clinics in low‐income, multicultural areas. Variables describing the trauma, socioeconomic status, direct and indirect costs, and time spent at the emergency visit for the dental trauma were retrieved from the dental records. The study also recorded which healthcare profession handled the first and follow‐up visits. Results: The prevalence of dental trauma in the study cohort was 8.2%, and higher among boys ( n  = 71) than girls ( n  = 39). Boys exhibited a significantly higher risk for dental trauma (OR, 1.76; 95% CI = 1.17–2.65). Maxillary incisors were the teeth most often traumatized, and lateral luxation was the most common diagnosis. The mean time spent per child during the first year following the dental trauma was 36 min, and the mean costs per child were EUR 878. The total average per‐child cost (direct and indirect costs) for dental trauma was EUR 2107. Dental visits due to traumatic injuries were significantly less common among children with an immigrant background and in families with an income ≤EUR 2000 per month. Conclusions: Toddlers in families who have a low socioeconomic status, a foreign background, and live in multicultural areas of Stockholm visit dental clinics for traumatic dental injuries less often than non‐immigrant children living in families with a high socioeconomic status.